Measuring consumption over the phone: Evidence from a survey experiment in urban Ethiopia - Abate, Gashaw T.; de Brauw, Alan; Hirvonen, Kalle; Wolle, Abdulazize (International Food Policy Research Institute, 2021)
The paucity of reliable and timely household consumption data in many low- and middle-income countries have made it practically impossible to assess how global poverty has evolved during the COVID-19 pandemic. Despite the burst of phone surveys, there has been few attempts to collect household consumption data. To test the feasibility of collecting consumption data over the phone, we conducted a survey experiment in urban Ethiopia, randomly assigning a balanced sample to either a phone or an in-person interview. The average value of per capita consumption is 23 percent lower, and the estimated poverty headcount is twice as high in the phone survey relative to the in-person survey. We see evidence of survey fatigue occurring early on in phone interviews but not in in-person interviews, and the bias is correlated with household characteristics. While the phone survey mode provides lower costs, it cannot replace in-person surveys for household consumption measurement.